Geophysical constraints for organic carbon sequestration capacity of Zostera marina seagrass meadows and surrounding habitats. (24th February 2017) - Miyajima, Toshihiro; Hori, Masakazu; Hamaguchi, Masami; Shimabukuro, Hiromori; Yoshida, Goro
Abstract: To elucidate the factors determining the organic carbon (OC) sequestration capacity of seagrass meadows, the distribution of OC and the fraction of seagrass‐derived OC in sediments of the temperate cosmopolitan seagrass Zostera marina meadows and surrounding habitats were investigated in relation to physical properties of sedimentary materials. On average, seagrass meadow sediments showed OC levels twofold higher than other shallow nearshore habitats. However, offshore sediments often showed greater OC concentrations than average seagrass meadow sediments. According to estimations of OC sources based on carbon isotope ratios, 8–55% and 14–24% of OC in nonestuarine seagrass meadow sediments and < 30 m deep offshore sediments, respectively, were assigned to seagrass origin. The OC concentration in seagrass meadow and offshore sediments closely correlated to the specific surface area (SSA) of sediment ( r 2 = 0.816 and 0.755, respectively; p < 0.0001), with an average OC loading per sediment surface area of approximately 60 μmol m −2 . In seagrass meadow sediments, the fraction of seagrass‐derived OC was also greater in samples with a larger SSA, and the seagrass‐derived OC occurred preferentially in sediment grains that had a specific gravity exceeding 2.0, namely, in a form closely associated with sediment minerals. The OC concentration, the fraction of seagrass‐derived OC, and the SSA were positively correlated to the logarithm of areal extent of individual seagrass meadows ( p < 0.01). These findings suggest that the OC sequestration capacity of nearshore vegetated habitats is under the primary control of geophysical constraints such as sediment supply rate and depositional conditions.